Dengue data and surveillance in Tanzania: a systematic literature review - Ward, Tara; Runge-Ranzinger, Silvia; Horstick, Olaf (Tropical medicine & international health, 2017)
Objective Although there is evidence that dengue virus is circulating in Tanzania, the country lacks a dengue surveillance system. Consequently, the true estimate of dengue seroprevalence, as well as the incidence in the population, the frequency and magnitude of outbreaks is unknown. This study therefore sought to systematically review available dengue data from Tanzania. Methods The systematic review was conducted and reported using the PRISMA tool. Five databases (PubMed, Embase, Web of Science, WHOLIS and Google Scholar) were searched for articles using various keywords on the illness, data and geographical location. Identified articles were assessed for inclusion based on predefined eligibility criteria. Data were extracted from included articles, analysed and reported. Results Based on the 10 seroprevalence studies in defined populations with estimates of acute confirmed infections that were included in the review, the estimated seroprevalence of past dengue infection in Tanzania ranged from 50.6% in a health facility-based study to 11% in a population-based study. Acute confirmed infections of dengue were estimated to be as high as 38.2% of suspected cases. Only one study reported on an outbreak. Conclusions It is evident that dengue needs to become part of regular disease surveillance in Tanzania. Control measures need to be instituted with a focus on building human resource capacity and integrating dengue control measures in ongoing health programmes, for both preventive and curative interventions. Systematic reviews are valuable in assessing health issues when surveillance data are not available.